Study of the Greater Caucasus glaciers and forest distribution routes - Baghirov Hussein (BIO Web of Conferences)
The glaciers of the Caucasus Mountains and their role in water bodies has been investigated in this topic. Changes in glaciers over time on the peaks of the Caucasus mountains Bazarduzu, Shahdag, Bazaryurd and Tufandag were analyzed as well. It has been determined that the role of glaciers in the formation of Gudyalchay and Gusarchay is exclusively important. A significant percentage of water flows into these rivers as a result of melting glaciers. The nature of the forests of the Greater Caucasus has been studied, and the ways of forest expansion have been investigated. The importance of glaciers and forests for nature conservation has been shown.